Ambient Turbulence Intensity Calculation for Al-Nasiriyah Province in Iraq - Saleh, Mohammed; Ani, Ayad; Hadi, Firas (Iraqi Journal of Science, 2023)
Before setting a turbine in a wind farms allocated for power generation, it must be know the appropriate turbine class for that site depending on the turbulence intensity of the winds in the studied area and the IEC-61400 standard. The importance of identifying a class of wind turbine is due to the complex environmental conditions that produce turbulent air which, in turn, may cause damage to the turbine blades and weakness in the performance. Therefore, the ambient turbulence intensity is a very important factor in determining the performance and productivity of the wind turbines.In this research we calculate Turbulence Intensity "TI" in the province of Nasiriyah, south of Iraq (Lat. 31.052049 , Lon. 46.261021) for the years 2008, 2009, and 2010, in addition to determine the wind turbine class that appropriate for the site after comparison with the Normal Turbulence Model "NTM" belongs to IEC 61400-1, edition2 and IEC 61400-1, edition3.